Judicial Review in Indonesia: A Simplification Model (Lex Scientia Law Review, 2022)
Judicial review ensures that no regulations are contrary to higher laws, and none is unfair to people. The review of Indonesia's laws and regulations is conducted based on a hierarchy of laws and regulations. However, many laws and regulations are not within the hierarchy that raises uncertainty about the institutions that are authorized to review them. This research aims to offer an alternative review authority against all types of laws and regulations applicable in Indonesia. This research employed normative legal research with statutory, conceptual, case, and historical approaches. This study stated that the alternative design of regulatory, judicial review is the unification of all judicial reviews' authority into one judicial institution. Second, separation into judicial institutions is different from the model of separation based on the order of hierarchy of legislation, based on the scope of usable power (local and national), based on legislation and non-legislation, based on the forming and separation institutions with cross-subsidy models.